Akomodasi Komunikasi dalam Komunikasi Antarbudaya antara Stranger dengan Host Culture (Etnis Jawa dengan Etnis Kutai) - Fitria Mahdiyyani, Anisah; Rahardjo, Turnomo; Sunarto, Sunarto (Jurusan Ilmu Komunikasi, FISIP, Universitas Diponegoro, 2021)
When Javanese ethnic (stranger) enters a new area with their original culture and dealing with a Kutai ethnic (host culture) who has a different culture, intercultural communication is established. However, these differences in cultural values and norms can trigger various problems and trigger ineffective communication due to lack of knowledge and lack of cultural understanding of each other. The purpose of this study is to know the description of the experience of inter-ethnic interaction and communication accommodation strategies carried out by Javanese and Kutai ethnic groups. The theories used are Communication Accommodation and Interaction Adaptation Theory. This research is a descriptive study with a case study approach to look at the case deeply and examine the experience of informants related to a phenomenon experienced with accommodation communication as a main focus. In this study, in-depth interview was used to three native Javanese (strangers) and three native Kutai ethnic (host culture) The study’s findings reveal that there is communication accommodation process between Javanese and Kutai ethnicities that does not always go without obstacles. The obstacles encountered in this study can be seen in terms of language, speech style, and habits. Afterwards, the majority of informants use a convergence strategy as a form of effort for the social interest, bridging cultural differences, and the desire to blend in with each other by negating their original cultural identity. Each individual also has stages of interacting and efforts to minimize misunderstandings when adapting in various ways.